2021
DOI: 10.1093/jmcb/mjab041
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted roles of centrosomes in development, health, and disease

Abstract: The centrosome is a membrane-less organelle consisting of a pair of barrel-shaped centrioles and pericentriolar material and functions as the major microtubule-organizing center and signaling hub in animal cells. The past decades have witnessed the functional complexity and importance of centrosomes in various cellular processes such as cell shaping, division, and migration. In addition, centrosome abnormalities are linked to a wide range of human diseases and pathological states, such as cancer, reproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 135 publications
(149 reference statements)
1
14
0
Order By: Relevance
“… 139 Therefore, it is not surprising that centrosome dysfunction is also closely associated with ciliopathy. 140 Moreover, primary cilia exist in hematopoietic cells and regulate the Hh signaling pathway. 141 Further, the number of primary cilia in AML cells decreases while the mutation frequency of primary cilia increases.…”
Section: Future Perspectivesmentioning
confidence: 99%
“… 139 Therefore, it is not surprising that centrosome dysfunction is also closely associated with ciliopathy. 140 Moreover, primary cilia exist in hematopoietic cells and regulate the Hh signaling pathway. 141 Further, the number of primary cilia in AML cells decreases while the mutation frequency of primary cilia increases.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In multicellular organisms including humans, the centrosome plays a critical role in the regulation of development and tissue homeostasis, often through its cell type–specific functions (Tang & Marshall, 2012 ; Araújo, 2019 ; Bornens, 2021 ; Qi & Zhou, 2021 ). As a prime example, in the Drosophila larval neural stem cell or neuroblast (NB), which undergoes stereotypical asymmetric cell division (Gallaud et al , 2017 ), the centrosome regulates spindle orientation and division axis maintenance through a unconventional behaviour specific to this cell type (Rebollo et al , 2007 ; Rusan & Peifer, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…An association between large vacuoles and sperm chromatin immaturity has been demonstrated ( 24 ). Recently, the focus was oriented on the sperm centriolar region, since, in humans, sperm itself contributes centrioles to the zygote ( 25 , 26 ). Fishman et al ( 27 ), using electron microscopy with high pressure freezing, demonstrated that in mature human spermatozoa two centrioles are present, revising the centrosome reduction dogma ( 28 ).…”
Section: Sperm Morphology At Transmission Electron Microscopy Levelsmentioning
confidence: 99%